Development of a Novel Immune Infiltration-Based Gene Signature to Predict Prognosis and Immunotherapy Response of Patients With Cervical Cancer - Yu, Sihui; Li, Xi; Zhang, Jiawen; Wu, Sufang (Frontiers in Immunology, 2021)
Predictive models could indicate the clinical outcome of patients with carcinoma. Cervical cancer is one of the most frequently diagnosed female malignancies. Herein, we proposed an immune infiltration-related gene signature which predicts prognosis of patients with cervical cancer and depicts the immune landscape as well. We utilized the transcriptome data of The Cancer Genome Atlas (TCGA) and estimated the infiltration level of 28 immune cell types. We screened out four immune cell types conducive to patient survival and recognized their shared differently expressed genes (DEGs). Four core genes (CHIT1, GTSF1L, PLA2G2D and GNG8) which composed the ultimate signature was identified via univariate and multivariate Cox regression. The optimal model we built up could distinguish patients with cervical cancer into high-score and low-score subgroups. These two subgroups showed disparity in aspects of patient survival, immune infiltration landscape as well as response to immune checkpoint inhibitors. Additionally, we found that GTSF1L was decreased gradually along with the severity of cervical lesions, and its potential role in immune contexture and clinical practice was also demonstrated. Our results suggested that the Immune Score based on four immune-related genes could serve as a supplementary criterion to effectively foresee the survival outcome, tumor infiltration status and immunotherapy efficacy of cervical cancer patients.